Genotoxic evaluation of ceftriaxone by in vivo micronucleus test in albino mice - Dayana, Kunjumon; Manasa, Megaravalli R. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Genotoxicity screening of drugs is essential. It is mandatory for new drugs. However, screening of drugs already in use is also necessary. Several cephalosporins are reported to induce chromosomal aberrations in previous studies. But there is paucity of data regarding the genotoxic potential of ceftriaxone. Hence the present study was undertaken to evaluate the genotoxic potential of ceftriaxone, a third generation cephalosporin, by micronucleus assay in albino mice. Methods: In vivo micronucleus test was performed with mice bone marrow after intraperitoneal injection of ceftriaxone at 100mg/kg BW and 200mg/kg BW at 24 hr and 48 hr harvest time. Mice bone marrow was harvested, and slides were prepared. The percentage of micronucleated polychromatic erythrocytes (% MnPCE) and the ratio of polychromatic erythrocytes to normochromatic erythrocytes (PCE:NCE) were determined. The data from ceftriaxone treated groups was compared with control group and analyzed using ANOVA followed by Dunnett’s test. Results: Ceftriaxone at the dose of 100mg/kg BW and 200mg/kg BW did not exhibit any significant increase in the percentage of micronucleated polychromatic erythrocytes. It also did not decrease the ratio of polychromatic erythrocytes to normochromatic erythrocytes significantly. Conclusions: The present study demonstrates that ceftriaxone is not genotoxic in in vivo micronucleus study in albino mice at a dose of 100mg/kg BW and 200mg/kg BW.